The Impact of Online Learning in Chemistry on Student Interest, Motivation and Learning Outcomes - Abdul Gani; Habibati Habibati; Febrina Aulia Putri (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
Unstable network connections, including chemistry learning, often hamper the implementation of online learning during a pandemic. The study aims to investigate the effects of online learning on chemistry students' interest, motivation, learning outcomes, and the challenges faced during the implementation. The method used is a quantitative method with descriptive research. Using the proportional stratified random technique, this study determined 72 high school students (33 boys and 39 girls). In online learning, data is collected using student and teacher response questionnaires. In addition, student reactions to teacher efforts in online learning. Then, interviews with teachers and students were conducted. Questionnaires and interview guidelines were used as research instruments. Data analysis techniques were used to determine respondents' level of achievement using the percentage formula (TCR). The study's findings revealed that the average response value for learning interest was 76%, motivation was 79%, and learning outcomes were 75%. Students achieve a minimum completeness criterion score of 81% for eleventh-grade students in the science program and 89% based on the results of the chemistry test scores in online learning. The study concludes that while online learning positively impacts students' interest, motivation, and learning outcomes, there are significant barriers identified by respondents, such as a less stable internet network, for further research is expected to be able to update the data taken by researchers.